2010
DOI: 10.1007/s10209-010-0217-5
|View full text |Cite
|
Sign up to set email alerts
|

Atlas.txt: exploring linguistic grounding techniques for communicating spatial information to blind users

Abstract: This paper describes exploratory research into automatically describing geo-referenced information to blind people. The goal is to produce texts giving an overview of the spatial layout, and a central concern of such texts is that they employ an appropriate linguistic reference frame which enables blind hearers to ground the information. The research presented in this paper was based on two hypotheses: (1) directly perceivable reference frames are easier to ground, and (2) spatial descriptions drawn from compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In a recent study, this idea was put to the test by finding out the most effective way to describe census data to people who are blind (Thomas, Sripada, & Noordzij, 2012). Census data often contain information about the frequency distribution of demographic variables (i.e., incidence of crime in different regions in a country).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, this idea was put to the test by finding out the most effective way to describe census data to people who are blind (Thomas, Sripada, & Noordzij, 2012). Census data often contain information about the frequency distribution of demographic variables (i.e., incidence of crime in different regions in a country).…”
Section: Discussionmentioning
confidence: 99%
“…audio and haptic), the project Atlas.txt [21] investigated how geo-referenced information (often conveyed via shaded thematic choropleth maps) can be communicated to blind users; the project developed a prototype data-to-text Natural Language Generation (NLG) system that produces textual summaries of UK 2001 Census data.…”
Section: Related Workmentioning
confidence: 99%
“…Navigation can be modeled as a sequence of locations and actions from an initial location to a target location. It has been shown that verbal descriptions are well suited to the description of human navigations [7,8,14]. Several recent studies have attempted to model navigation knowledge from human verbal descriptions [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, and despite the fact that humans are effective to process and transmit such knowledge, there is still a conceptual gap between these descriptions and map representations. Other approaches in indoor or outdoor environments have been suggested to model verbal routes descriptions [8,14].…”
Section: Introductionmentioning
confidence: 99%